UMA ð˜Žð˜³ð˜¢ð˜µð˜ªð˜¥ð˜ªð˜¢ NOVA DO BRASIL (PHASMIDAE â€“ PACHYMORPHINAE) - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2020)
UMA ð˜Žð˜³ð˜¢ð˜µð˜ªð˜¥ð˜ªð˜¢ NOVA DO BRASIL (PHASMIDAE â€“ PACHYMORPHINAE)